2023
DOI: 10.14202/vetworld.2023.483-490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of goat management systems on hematological, oxidative stress profiles, and parasitic gastrointestinal infection

Abstract: Background and Aim: Good management in goats is known for good quality health and increasing productivity. The physiological change studies in goats are limited despite some existing studies on the relationship of various patterns to growth rates. This study aimed to determine the hematological parameters, oxidative stress, and parasitic infection in three management systems in Thai native goats. Materials and Methods: A total of 18 male goats were randomly assigned to the three systems: The free-range model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Impliedly, in response to the different surgical techniques used in groups A, B, and D, the goats might have activated compensatory mechanisms to maintain homeostasis, preventing significant alterations in hematological parameters, much so close to the findings of Alvites et al (2021), who observed in their study reviews which summarized the general principles related to the use of small ruminants as animal models for scientific research. A study by So-In and Sunthamala (2023) on housing systems used for goat management highlighted similar influences on hematology, and stress profiles in goats. Although the surgical technique for rumenotomy differed between groups A and B of the same lateral recumbency restraint position, it is possible that the variation in technique did not have a substantial impact on the measured hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Impliedly, in response to the different surgical techniques used in groups A, B, and D, the goats might have activated compensatory mechanisms to maintain homeostasis, preventing significant alterations in hematological parameters, much so close to the findings of Alvites et al (2021), who observed in their study reviews which summarized the general principles related to the use of small ruminants as animal models for scientific research. A study by So-In and Sunthamala (2023) on housing systems used for goat management highlighted similar influences on hematology, and stress profiles in goats. Although the surgical technique for rumenotomy differed between groups A and B of the same lateral recumbency restraint position, it is possible that the variation in technique did not have a substantial impact on the measured hematological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…After that, the samples were heated to a 15-min boil. The thiobarbituric acid-reactive species was measured with a spectrofluorometer that was calibrated to emit at 551 nm and excite at 528 nm ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Improvements in nutrition during fetal hair follicle formation are important for increasing secondary hair follicle size, depth, and density. Maternal nutritional deficiency and oxidative stress damage during pregnancy, including a hightemperature environment and insufficient maternal oxygen supply, adversely affect the development of fetal secondary hair follicles [6][7][8]. In practice, a series of problems, such as bad environmental conditions, single forage types, and extensive feeding management, can lead to the oxidative stress of goats, resulting in an increase in free radical generation in the body and, subsequently, a change in the physiological state [7,9].…”
Section: Introductionmentioning
confidence: 99%